Econometric model for measuring the impact of the education level of the population on the recycling rate in a circular economy - Corina Pelău; Alexandra Cătălina Chinie (Amfiteatru Economic Journal, 2018)
Due to the positive effect it has on the environment, while also creating social and economic value, recycling represents a key factor in the realization of a circular economy and of sustainable development. For the implementation of efficient programs, the recycling rate has become a relevant subject to public institutions, but also for the academia, companies and non-profit associations. The objective of this article is to determine the influence of the population's level of education on the recycling rate of waste. The article has a contribution to the scientific literature, by analyzing the correlation between education and the recycling rate in Europe, with living conditions and internet access as control variables. Results of a panel data analysis show that a high percentage of the population with only primary or lower secondary education, influence negatively the recycling rate of waste in an economy, while tertiary education has a positive influence on the level of recycled waste. Therefore, different policies which aim to increase the education level of the population will have an effect on the recycling rate.
Keywords: Q53; 330; recycling; circular economy; sustainable consumption; municipal waste; education level; panel data analysis